Incarner un modèle progressiste La professionnalisation de l'enseignement à Chicago (1890-1940) - Birocheau, Sonia (Éducation et savoirs en société, 2020)
The 1890s to 1940s were a pivotal era in the development of a professionalised approach to teaching in the United States. Reforms that were seen as beneficial to society were led by a variety of actors who sought to change how teachers were trained, the teaching methods used, and how school systems were organised. Chicago was a leading centre of reflection in these progressive projects aimed at professionalising teaching. This book offers a historical study of these transformations based on a large and unprecedented sample of actors, institutions and sources. What role did teachers, principals and staff at the Chicago Normal School play in shaping and promoting new professional paradigms? To what extent were these new models put into practice on a daily basis in schools? What was the real scale and content of this professional conquest? This case study provides a complementary perspective on the history of North American education, progressivism, and Chicago, and addresses themes that resonate with today's reflections on teaching, gender, and race relations.